Numerical simulation of cryotherapy on a hepatocellular carcinoma (Damascus University Journal for engineering sciences, 2023)
Cancer is a leading cause of death worldwide, claiming 10 million lives in 2020. Cancer arises from the transformation of normal cells into neoplastic cells in a multistage process that generally progresses from a precancerous lesion to a malignant tumor. The correct diagnosis of cancer is indispensable to treat it properly and effectively, because each type of cancer requires a specific course of treatment, and its treatment usually includes radiotherapy, chemotherapy, surgery or combined with each other, and new techniques are currently used, namely, heat therapy by cooling or heating.In this paper, we present a simulation of cryotherapy for cancer by studying a liver tumor model. Where a 3D model of the tumor located in the liver was built based on the medical images taken from a computed tomography device and then retrieved these images to a simulation program for thermal mapping during treatment in three cases using one or two probes or three treatment probes.The study concluded that the treatment method used is highly effective in killing cancer cells, while achieving a great safety percentage for healthy tissues, with the treatment time varying according to the number of treatment probes
Keywords: cancer; heat treatment; cooling